2021
DOI: 10.37190/abb-01868-2021-03
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring weakness at 90° flexion of involved knee as an indicator of the function deficit in males after anterior cruciate ligament reconstruction (ACLR)

Abstract: Purpose: The aim of this study was to elucidate predictors on knee function following anterior cruciate ligament reconstruction with hamstring tendon graft or allograft and to detect the differences between it and the healthy controls. Methods: This study comprised of 46 males, aged 18–45, being within 6–60 months following unilateral anterior cruciate ligament reconstruction and 50 healthy men. Measurements included the Tampa Scale for Kinesiophobia-17, the self-reported knee function with the Knee Injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…24 There is also a decrease in knee flexion muscle strength, which can cause functional limitations, especially in daily activities and sports that demand an increase in knee flexion muscle contraction. 12 In post-ACL reconstruction patients, quadriceps strength LSI correlates more strongly with future knee function and activity levels than hamstring strength LSI. Isotonic and isokinetic hamstring power LSI is also highly related to the Lysholm score, which evaluates knee function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…24 There is also a decrease in knee flexion muscle strength, which can cause functional limitations, especially in daily activities and sports that demand an increase in knee flexion muscle contraction. 12 In post-ACL reconstruction patients, quadriceps strength LSI correlates more strongly with future knee function and activity levels than hamstring strength LSI. Isotonic and isokinetic hamstring power LSI is also highly related to the Lysholm score, which evaluates knee function.…”
Section: Discussionmentioning
confidence: 94%
“…11 In addition, decreased knee flexion strength in the hamstring muscles can also cause functional limitations, especially in daily activities or sports requiring increased knee flexion. 12 ACL damage directly causes a loss of plantar flexion strength in the gastrocnemius muscle linked to the knee joint. 13 Weakness in the gluteus maximus increases the risk of ACL damage because the capacity to resist internal rotation of the tibia is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective cohort study carried out by Horteur et al [19], pointed out that the utilization of HST grafts results in a decrease their contractile capacity as the diminishment observed the quadricipital musculature. Besides, Balki et al [20] also linked a reduction in HST motor strength following ACL reconstruction with a less favorable prognosis in terms of knee functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another study also reported that hamstring strength deficits were found in the HT group during knee extension. 21 This occurs due to the retrieval of quadriceps and hamstring tendons, causing functional limitations in the movement of post-ACLR patients.…”
Section: Discussionmentioning
confidence: 99%